Analysis of Marketing Performance Using Purchase Intention and Purchase Decision (Case of Electric Vehicles in China) - LIU, XU; Jokhu, Jean Richard (Lentera Ilmu Madani, 2024)
Among the negative effects of modern society, global warming is a major problem. It is especially important for countries to realize that reducing greenhouse gas emissions through the transition to electric vehicles. Therefore, this study aims to analyze the factors that affect the purchase intention of electric vehicles. This study utilized quantitative research by SPSS to analyze multiple linearity and other analysis through the 252 questionnaires collected. The Chinese respondents in the study all met the screening criteria of having owned or driven an electric vehicle. It was found that among the four independent variables function value (FV), price (P), brand trust (BT), and attitude (A), only the variable price did not have a significant effect on the dependent variable purchase intention (PI). Consistent with previous research findings, purchase intention (PI) continues to have a positive effect on purchase decision (PD).